PELAKSANAAN TEKNOLOGI INFORMASI PADA KUALITAS LAYANAN ADMINISTRASI MAHASISWA DI KAMPUS UNIVERSITAS PASIR PENGARAIAN - Rahayu, Heffi Christya (E-Journal Cano Ekonomos, 2013)
The focus of this research is the implementation of the Information Technology Services Quality of Student Administration at University Campus of Pasir Pengaraian. With the formulation of the problem is How the implementation of information technology on the quality of administrative services at the University of sand Pengaraian. The method used in this study is quantitative Diskriftif. The population in this study were university students as much Pasir Pengaraian 1713 people, with a total sample of 50 respondents. Data was collected through observation, interviews and questionnaires deployment. To analyze the data using simple regression analysis. Based on the scores obtained from the results of the study showed that, concluded the majority of respondents chose the answer that information technology at the University of Pasir Pengaraian unfavorable. Most of the respondents chose the answer that the quality of academic services at the University of Pasir Pengaraian well. The results of the above data processing questionnaires concluded that most respondents either academic services. Regression equation Y = 1.347 X 0.433 of these equations can be seen the influence of information technology variables (X) with the variable quality of academic services (Y). If the value of information systems up one unit of the value of quality of service will increase 0.433 units. This means that information technology is increasing the quality of service will increase, and vice versa.